The Relationship between Spending Per Person and Outcomes Achieved by Intellectually and Developmentally Disabled Americans - Coons, Timothy (My University, 2023)
The care and fair treatment of individuals diagnosed with intellectual and developmental disabilities (IDD) is a globally evolving concern. Within the United States, federal and state governments along with private sector organizations are tackling issues relating to housing, victimization, lack of financial resources, healthcare, loneliness, and quality of life of individuals diagnosed with IDD. Central to the issue of improved outcomes for the group are the associated costs. Most individuals in the U.S. diagnosed with IDD do not have income or assets sufficient to cover costs associated with their care. Therefore, federal and state governments have assumed the greatest share of associated costs. The purpose of this study is to determine whether relationships exist between state and federal funding allocations and outcomes achieved by individuals diagnosed with IDD. This study employs One-Way Analysis of Variance and Linear Regression methods to evaluate per person spending and quality of life outcomes achieved by individuals diagnosed with IDD residing in as many as 41 states and municipalities during years 2011, 2013 and 2015 using publicly available data. The study found that in all but one instance the amount of money allocated to provide care for individuals diagnosed with IDD was not significantly correlated to quality-of-life outcomes achieved by these individuals.
Chapter I: INTRODUCTION 1 -- Background 1 -- Purpose of the Study 3 -- Statement of the Problem 4 -- Research Question 6 -- Researcher Relationship to IDD Population 6 -- Bias 7 -- Chapter II: REVIEW OF LITERATURE 9 -- Intellectual Disability or Developmental Disability 9 -- Prevalence 10 -- Person First Language and Elimination of Mental Retardation 12 -- Limited Research Conducted on IDD Population 14 -- History 17 -- Victimization 20 -- Financial Support 22 -- Medicaid 24 -- Home and Community Based Services 28 -- Affordable Care Act 32 -- Healthcare 34 -- Loneliness 39 -- Public Management/ Public Policy 41 -- Chapter III: METHODOLOGY 42 -- Overview 42 -- Data Source 42 -- Independent Variable 46 -- Dependent Variables 46 -- Hypotheses 46 -- Control Variables 48 -- Analytic Procedures 49 -- Study Limitations 50 -- Chapter IV: RESULTS 51 -- Overview 51 -- Descriptive Statistics 59 -- Bivariate Correlation Analysis 64 -- Regression Analysis 70 -- Individuals diagnosed with IDD reporting having someone to go to for help if they feel scared 70 -- Individuals diagnosed with IDD reporting loneliness 72 -- Individuals diagnosed with IDD reporting having friends who are not paid staff or family 73 -- Individuals diagnosed with IDD reporting receiving annual health examinations 75 -- Individuals diagnosed with IDD reported to be overweight or obese 76 -- Individuals diagnosed with IDD reporting exercise 30 minutes three times weekly 78 -- Chapter V: CONCLUSION 81 -- Summary of Findings 81 -- Recommendations 83 -- Study Limitations 85 -- Future Research 86 -- REFERENCES 88.
Keywords: Public administration; Dissertations, Academic; Developmental disabilities